Mekanisme Pembatalan Perkawinan Dan Implikasinya Terhadap Hak Perempuan Atas Poligami Tanpa Izin Di Indonesia - Alfiyah Faizatul Arif (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2021)
Abstract: A marriage can be broken up due to death, divorce and decisions of a religious court. Both due to divorce and annulment of marriage. Annulment of marriage can be filed for a variety of reasons, one of which is a polygamy committed without the permission or knowledge of the first wife. Then it has an impact on a marriage that is considered unprecedented. However, it is still a question of all the consequences and impacts therein. Using a normative juridical approach, this paper discusses how annulment of marriage in the practice of religious court law and what rights women get after the annulment of marriage. This paper argues that the mechanism of annulment of marriage for unlicensed polygamy resulting in marriage being considered to have not effect on the confusion of women's rights. Â Keywords: Annulment of marriage, Polygamy without the permission, and Womenâ€™s right.